Penerapan Tembang Dolanan Anak Melalui Model Pembelajaran Project Based Learning (PJBL) Untuk Peningkatan Kompetensi Kecintaan Budaya Nasional - Agung Tri Susilo Raharjo; Moh. Rusnoto Susanto; Hesti Ratnasari; Mela Dina Arumsari (Adi Karsa: Jurnal Teknologi Komunikasi Pendidikan, 2025)
The application of cultural arts learning in elementary schools. Educators or teachers certainly have learning models that are in accordance with the material to be delivered . This learning model is very important because with the right learning model it will trigger students to be active and creative. The aplication of childrens song through the Project Based learning (PJBL) learning model that guides student to increase creativity in learning . The purpose of this study was to determine the understanding of studentin learning cultural arts with the media of Javanese children”s songs in elementary school. This research uses a qualitative descriptive method by describing the results of the analysis of research findings . Data collection techniques using observation, interviews and documentation. The result of the study show that the Project Based Learning model is very appropriate to be applied to increase the of students in SBdP learning through Javanese childrens songs or songs of Javanese childrens songs. It is evident from 28 students that there are 2 students who have not developed, 10 students are developed as expected, 3 students are developing very welll. The conclusion is that the innovation of learning Javanese childrens songs or through the Project Based Learning (PJBL) model thourgh media is very influential on improving SBdP learning in class IV elementary schools.